2011
DOI: 10.1590/s0103-50532011000100015
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of food dyes by zero-valent metals exposed to ultrasonic irradiation in water medium: optimization and electrospray ionization mass spectrometry monitoring

Abstract: A degradação redutiva de quatro corantes típicos (Azul Brilhante, Amaranto, Amarelo Crepúsculo e Vermelho 40), largamente empregados pela indústria alimentícia, por metais de valência zero (Fe e Sn), sob irradiação ultrassônica (US) em meio aquoso ácido (pH 3,0), foi estudada. As reações foram monitoradas por ESI(-)-MS (espectrometria de massas com ionização electrospray no modo negativo), além de espectrofotometria UV-Vis e carbono orgânico total (TOC). A influência de parâmetros preponderantes (tempo de expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
11
0
1
Order By: Relevance
“…Studies have shown that amaranth can cause many adverse health effects, such as high genotoxicity, cytostaticity, and cytotoxicity 17. In the last few years, several studies have been performed on the degradation of amaranth in aqueous solution by hypochlorite,18 zerovalent metals (Fe and Sn) under ultrasonic irradiation,19 electrochemical processes,20 advanced oxidation processes using UV/TiO 2 14, 21 or UV/TiO 2 /O 3 ,21 and biological oxidation 15. The oxidation of amaranth by an advanced photo‐Fenton process in the presence of some aromatic derivatives such as hydroquinones, chlorophenol, dichlorobenzene, aromatic carboxylic acids, anilidine, and nitrophenol has also been investigated recently 22…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that amaranth can cause many adverse health effects, such as high genotoxicity, cytostaticity, and cytotoxicity 17. In the last few years, several studies have been performed on the degradation of amaranth in aqueous solution by hypochlorite,18 zerovalent metals (Fe and Sn) under ultrasonic irradiation,19 electrochemical processes,20 advanced oxidation processes using UV/TiO 2 14, 21 or UV/TiO 2 /O 3 ,21 and biological oxidation 15. The oxidation of amaranth by an advanced photo‐Fenton process in the presence of some aromatic derivatives such as hydroquinones, chlorophenol, dichlorobenzene, aromatic carboxylic acids, anilidine, and nitrophenol has also been investigated recently 22…”
Section: Introductionmentioning
confidence: 99%
“…For E132, the degradation ratio in the presence of ZnO and H2O2 is 69.47 % at 2 min and 97.1% and at 10 min irradiation time for 10 mg L -1 and 50 mg L -1 respectively. Importantly, there was no emergence of new absorption bands after 8 min and 2 min reaction time for E127 and E132 respectively, thus suggesting the presence of by-products (possibly formed under these conditions) [10]. These results indicate that these food dyes can be degraded to a certain extent under ultrasonic dye combined with ZnO powder and H2O2.…”
Section: Effect Of Initial Dye Concentrationmentioning
confidence: 70%
“…The spectra show a clear decrease in the maximum absorption wavelength in the visible region (λ max) for each dye and a hypsochromic shift occurred simultaneously with increasing sonication time *38, 40+. Most importantly, after 30 min of reaction time, no emergence of new absorption bands for E132 and E127 was observed indicating a possible formation of by-products under these conditions as revealed by the low mineralization rates [10].…”
Section: Comparison Of Removal Efficiency Of Food Dyes Using Us Znomentioning
confidence: 90%
See 2 more Smart Citations